Association between weight-adjusted waist index and chronic obstructive pulmonary disease - Xingshi Hua; Yu Gan; Xiaodong Lv (PLoS ONE, 2025)
Objective This study aimed to investigate the association between the weight-adjusted waist index (WWI), a novel obesity metric, and the prevalence of chronic obstructive pulmonary disease (COPD) in a nationally representative sample of U.S. adults, and to compare its predictive utility for COPD against conventional obesity indices. Methods This cross-sectional study utilized data from the 2017–2020 National Health and Nutrition Examination Survey (NHANES). COPD diagnosis was based on self-report. The association between WWI and COPD was investigated using multivariable logistic regression models, adjusting for key covariates including age, gender, race/ethnicity, smoking status, hypertension, and diabetes. Restricted cubic splines (RCS) were used to explore potential non-linear relationships. Receiver operating characteristic (ROC) curves were used to assess WWI’s predictive performance. All statistical analyses were conducted using R software, accounting for the complex survey design and weighting. Results This study comprised 3,111 participants, among whom the prevalence of COPD was 8.5%. The findings indicated a significant positive association between WWI and the prevalence of COPD (OR = 1.30, 95% CI: 1.02–1.66). When analyzed by quartiles, a significant positive dose-response relationship was observed ( P for trend = 0.031). Furthermore, receiver operating characteristic (ROC) analysis revealed that WWI had significantly better predictive performance for COPD (Area Under the Curve [AUC] = 0.662) than conventional obesity indices. Conclusion Our findings suggest a significant positive association between WWI and the self-reported prevalence of COPD. WWI shows promise as a simple, non-invasive anthropometric tool that may aid in identifying individuals with higher odds of having COPD in clinical and public health settings.